2017
DOI: 10.1186/s12905-017-0482-z
|View full text |Cite
|
Sign up to set email alerts
|

Using theory-based messages to motivate U.S. pregnant women to prevent cytomegalovirus infection: results from formative research

Abstract: BackgroundAn estimated 1 in 150 infants is born each year with congenital cytomegalovirus (CMV); nearly 1 in 750 suffers permanent disabilities. Congenital CMV is the result of a pregnant woman becoming infected with CMV. Educating pregnant women about CMV is currently the best approach to prevention. Limited research is available on how to effectively communicate with women about CMV. We conducted formative research on fear appeals theory-based messages about CMV and prevention with U.S. women. Fear appeal th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…The correlation between CMV awareness and the recency of pregnancy, as seen in this study, is also consistent with the ndings reported by others 22,44 , indicating the success of information campaigns in the US about CMV. Certainly, individuals most concerned about cCMV disease are motivated by the desire to increase their likelihood of having a healthy baby 45 . In contrast to reports on other vaccines showing higher acceptance rates in older individuals 46 , the opposite was observed here.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between CMV awareness and the recency of pregnancy, as seen in this study, is also consistent with the ndings reported by others 22,44 , indicating the success of information campaigns in the US about CMV. Certainly, individuals most concerned about cCMV disease are motivated by the desire to increase their likelihood of having a healthy baby 45 . In contrast to reports on other vaccines showing higher acceptance rates in older individuals 46 , the opposite was observed here.…”
Section: Discussionmentioning
confidence: 99%
“…As shown by a study conducted in France, the rate of primary CMV infection during pregnancy is influenced by hygiene counseling [ 50 ]. Current research focuses on strategies for teaching pregnant or pregnant to be women and empowering them to adopt new habits to prevent CMV infections [ 51 ].…”
Section: Discussionmentioning
confidence: 99%